Fenomena Thrifting sebagai Gaya Hidup Milenial Bogor - Rifky Ghilmansyah; Siti Nursanti; Wahyu Utamidewi (Universitas Merdeka Malang, 2022)
Thrifting is an activity to buy used goods or can be called a saving method. Thrifting currently continues to be a trend for some people, especially for millennials because now there are many people or shops starting to sell used goods and there has been a thrifting event like in Bogor, namely the Bogor thrift market. This study aims to explain that there is a motive or purpose behind the Bogor millennials carrying out thrifting activities. This study also reveals how Bogor millennials interpret thrifting itself and the lifestyle methods developed by Bogor millennials who carry out thrifting activities. This study uses a phenomenological method with a qualitative approach. The approach used in this research is Alfred Schutz's phenomenological approach. In this approach there are 'because of motive' and 'in order to motive' from the actions of the Bogor millennials who carry out thrifting activities. With 5 speakers, namely Bogor millennials who like to do thrifting who have certain criteria and are willing to participate in this research until the end. The results of this study are showing that the Bogor millennials interpret thrifting as a process of shopping for used goods that has become a passion or lifestyle for fashion trends. They do thrifting because of the environment of friends, family, hobbies, and the economy, while the reason they want to achieve is because the price is relatively cheap, limited, high value and for resale.Keywords : Thrifting,lifestyle,fashion ,fenomenologi